Imaging the passionate stage of romantic love by dopamine dynamics - Takahashi, Kayo; Mizuno, Kei; Sasaki, Akihiro T.; Wada, Yasuhiro; Tanaka, Masaaki; Ishii, Akira; Tajima, Kanako; Tsuyuguchi, Naohiro; Watanabe, Kyosuke; Zeki, Semir; Watanabe, Yasuyoshi (Frontiers in Human Neuroscience, 2015)
Using [11C]raclopride, a dopamine D2/D3 receptor antagonist, we undertook a positron emission tomography (PET) study to investigate the involvement of the dopaminergic neurotransmitter system when subjects viewed the pictures of partners to whom they were romantically attached. Ten subjects viewed pictures of their romantic partners and, as a control, of friends of the same sex for whom they had neutral feelings during the PET study. We administered [11C]raclopride to subjects using a timing for injecting the antagonist which had been determined in previous studies to be optimal for detecting increases in the amount of dopamine released by stimulation. The results demonstrated statistically significant activation of the dopaminergic system in two regions, the medial orbitofrontal cortex and medial prefrontal cortex, the former of which has been strongly implicated in a variety of rewarding experiences, including that of beauty and love. A positive correlation was obtained in medial orbitofrontal cortex between excitement levels and dopaminergic activation only in the love but not in the control condition.